SOCIAL ADAPTATION OF CHILDREN IN KINDERGARTEN OF PRESCHOOL AGE (Web of Humanities: Journal of Social Science and Humanitarian Research, 2023)
The article discusses the directions of social adaptation of preschool children. Problems related to this, methods of adaptation of children